Exercise intervention regulates gut microbiota to improve type 2 diabetes: a narrative review of the mechanisms - Fang, Yifan; Cai, Yiwen; Chen, Xumin; Lin, Zhiyi (Frontiers in Nutrition, 2025)
BackgroundThe gut microbiota is increasingly recognized as a key factor in the pathogenesis of type 2 diabetes mellitus (T2DM). Concurrently, exercise intervention has emerged as a promising non-pharmacological strategy for T2DM management, potentially mediated through gut microbiome modulation.MethodsThis narrative review searched Web of Science, PubMed, and Embase for literature published from 1992 to the present, ultimately including 58 relevant publications. The focus was on elucidating the physiological mechanisms by which exercise modulates gut microbiota to ameliorate T2DM.ResultsOur synthesis indicates that exercise training beneficially alters gut microbiota composition and function, which in turn enhances systemic insulin sensitivity and improves metabolic disturbances in T2DM. These improvements are mediated through multiple pathways, including bile acid metabolism, short-chain fatty acid production, lipopolysaccharide reduction, and branched chain amino acid catabolism. The effects of exercise on the gut microbiome are influenced by factors such as exercise intensity, duration, and type, suggesting the need for individualized regimens.ConclusionExercise intervention improves T2DM by modulating gut microbiota via several mechanistic pathways. Future research should prioritize personalized exercise prescriptions, larger sample sizes, integrated multi-omics approaches, and exploration of combined interventions with diet or medication to optimize T2DM prevention and treatment.